Decision Support System Determination Of Contractemployees To Be Permanent Employees Using The Technique For Order Preference By Similarity To Ideal Solution (TOPSIS) Method - Mochzen Gito (RISTEC : Research in Information Systems and Technology, 2020)
PT. Refratech Mandala Perkasa (RMP) is a refractory cement manufacturing company. This company also operates in the manufacture of refractory cement which is made for the repair of hot coatings, boilers, rotary kilns, incinerators, ovens and chemicals. In this company there are contract employees and permanent employees, contract employees are employees or workers whose tenure is limited by a certain time. according to the agreement within the company. While permanent employees are workers whose working period is approximately until they receive certain benefits according to the work agreement. The purpose of this research is how to design and build a decision support system that can assist in determining contract employees to become permanent employees. This study uses the Technique For Order of Preference by Similarity to Ideal Solution (TOPSIS) method. The results of this study indicate that the determination of the ranking of prospective permanent employees can be obtained from the calculation of the TOPSIS method, where the results of prospective employees are based on predetermined administrative criteria. Prospective permanent employees who have the highest rank have the right to be surveyed first. The accuracy of the implementation of the TOPSIS method on the system plays a major role in the effectiveness and efficiency of the company's services to consumers compared to before the system was implemented. With the implementation of this DSS system, it can help companies to make it easier to make decisions to survey prospective permanent employees and optimize employee performance.PT. Refratech Mandala Perkasa (RMP) is a refractory cement manufacturing company. This company also operates in the manufacture of refractory cement which is made for the repair of hot coatings, boilers, rotary kilns, incinerators, ovens and chemicals. In this company there are contract employees and permanent employees, contract employees are employees or workers whose tenure is limited by a certain time. according to the agreement within the company. While permanent employees are workers whose working period is approximately until they receive certain benefits according to the work agreement. The purpose of this research is how to design and build a decision support system that can assist in determining contract employees to become permanent employees. This study uses the Technique For Order of Preference by Similarity to Ideal Solution (TOPSIS) method. The results of this study indicate that the determination of the ranking of prospective permanent employees can be obtained from the calculation of the TOPSIS method, where the results of prospective employees are based on predetermined administrative criteria. Prospective permanent employees who have the highest rank have the right to be surveyed first. The accuracy of the implementation of the TOPSIS method on the system plays a major role in the effectiveness and efficiency of the company's services to consumers compared to before the system was implemented. With the implementation of this DSS system, it can help companies to make it easier to make decisions to survey prospective permanent employees and optimize employee performance.